Pelatihan Model Pengembangan Kurikulum 2013 - Ahmad Ahmad; Edi Ardian; A. Muthalib; Edi Susrianto IP; Khairuddin Khairuddin (STAI Auliaurrasyidin Tembilahan, 2022)
The curriculum as several educational plans needs to be developed dynamically according to the needs and changes that occur in society with reference to the development of curriculum models. In line with this, among the many models of curriculum development, one that must be considered is choosing a curriculum development model. The selection of the development model is not based on the advantages and benefits and opportunities for optimal results, but also needs to be adapted to the education system and education processing system adopted and which educational concept model is used. serves as a means to facilitate a communication, or as a perspective guide for making decisions, or as a planning guide Therefore, the model can help us form the concept of the process by showing certain principles and procedures, as for the purpose of this mentoring is to provide insight to teachers in the development of the 2013 curriculum model. In addition, teachers who pursue escape are expected to improve their skills in carrying out learning activities. To achieve the expected goals of this training, lectures, demonstrations, exercises and assignments are used. The targets in this service are teachers SMA Tengku Sulung districts Sungai Batang. The methods used are in the form of seminars, demonstrations, and exercises or assignments.